Evolution of Oviposition Techniques in Stick and Leaf Insects (Phasmatodea) - Robertson, James A.; Bradler, Sven; Whiting, Michael F. (Frontiers in Ecology and Evolution, 2018)
Stick and leaf insects (Phasmatodea) are large, tropical, predominantly nocturnal herbivores, which exhibit extreme masquerade crypsis, whereby they morphologically and behaviorally resemble twigs, bark, lichen, moss, and leaves. Females employ a wide range of egg-laying techniques, largely corresponding to their ecological niche, including dropping or flicking eggs to the forest floor, gluing eggs to plant substrate, skewering eggs through leaves, ovipositing directly into the soil, or even producing a complex ootheca. Phasmids are the only insects with highly species-specific egg morphology across the entire order, with specific egg forms that correspond to oviposition technique. We investigate the temporal, biogeographic and phylogenetic pattern of evolution of egg-laying strategies in Phasmatodea. Our results unequivocally demonstrate that the ancestral oviposition strategy for female stick and leaf insects is to remain in the foliage and drop or flick eggs to the ground, a strategy that maintains their masquerade. Other major key innovations in the evolution of Phasmatodea include the (1) hardening of the egg capsule in Euphasmatodea; (2) the repeated evolution of capitulate eggs (which induce ant-mediated dispersal, or myrmecochory); (3) adapting to a ground or bark dwelling microhabitat with a corresponding shift in adult and egg phenotype and egg deposition directly into the soil; and (4) adhesion of eggs in a clade of Necrosciinae that led to subsequent diversification in oviposition modes and egg types. We infer 16 independent origins of a burying/inserting eggs into soil/crevices oviposition strategy, 7 origins of gluing eggs to substrate, and a single origin each of skewering eggs through leaves and producing an ootheca. We additionally discuss the systematic implications of our phylogenetic results. Aschiphasmatinae is strongly supported as the earliest diverging extant lineage of Euphasmatodea. Phylliinae and Diapheromerinae are both relatively early diverging euphasmatodean taxa. We formally transfer Otocrania from Cladomorphinae to Diapheromerinae and recognize two tribes within Diapheromerinae: Diapheromerini sensu nov. and Oreophoetini sensu nov. We formally recognize the clade comprising Necrosciinae and Lonchodinae as Lonchodidae stat. rev. sensu nov.